PENDEKATAN HERMENEUTIKA TERHADAP GERAKAN GENDER (INTERPRETASI AMINA WADUD) - Muhammad Ilham Thayyibi; Sedya Santosa (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2022)
Inequality regarding gender bias is a rather complicated problem. This happens because the problem is a product of the social construction of a patriarchal society. Worse yet, this is supported by the interpretation of the Qur'an which in fact is only done by men. This has an impact on interpretations that are gender biased, without glancing at the perceptions, goals, and characteristics of women. This problem initiated Amina Wadud to reconstruct the interpretation of the Koran so that there would be a product of interpretation that was female in style and seemed fair or equal. In interpreting the Qur'an, Amina Wadud uses the hermeneutic approach offered by Fazlur Rahman. So Amina Wadud views that the origins and potentials of men and women are the same regardless of gender differences. The purpose of this study is to find out what Amina Wadud's view of the creation of man and the Koran's view of women are like. The research method that the author uses is qualitative research with a library research approach that is relevant to the object of discussion. Data collection technique in this research is documentation technique. Documentation technique is data collection by selecting data that correlates with the research title.